2015
DOI: 10.1039/c5tb00431d
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the stability of chitosan/tripolyphosphate micro- and nanogels: resolving the opposing findings

Abstract: Micro-and nanogels prepared by ionically crosslinking chitosan with tripolyphosphate (TPP) attract keen interest as potential drug carriers. To achieve their optimal performance, it is essential to control their stability to aggregation and dissolution. Yet, literature on this subject (especially at physiological ionic strength and pH) remains filled with opposing reports. Recently, one of us hypothesized that these conflicting findings might stem from: (1) variations in the chitosan molecular structure;(2) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 48 publications
5
49
0
Order By: Relevance
“…In a similar situation, the increased ionic strength of the 150 mM NaCl solution, in which TPP‐chitosan micro‐ and nanogel particles were dispersed, caused the monovalent ions of NaCl to displace TPP. The same authors also reported the dissolution of the chitosan‐TPP particles upon increasing the pH to 7.2 …”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In a similar situation, the increased ionic strength of the 150 mM NaCl solution, in which TPP‐chitosan micro‐ and nanogel particles were dispersed, caused the monovalent ions of NaCl to displace TPP. The same authors also reported the dissolution of the chitosan‐TPP particles upon increasing the pH to 7.2 …”
Section: Resultsmentioning
confidence: 81%
“…The high concentration of the NaHCO 3 (0.6M) increased the ionic strength of the gelling solution. This increased ionic strength weakened the chitosan‐TPP ionic cross‐linking . The chitosan‐TPP ionic cross‐linking could have also been weakened as a result of the increased pH of the 0.6 M NaHCO 3 ‐supplemented gelling solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, a variety of strategies have been developed for removing heavy metals from wastewater and soil; however, some of these are limited due to issues with subsequent applications. 12 These nanoparticles often show wide biocompatibility and stability in a number of applications, such as the separation of heavy metals. 5,6 For the purpose of Ni 2+ removal, multiple technologies have been employed, such as chemical precipitation, 7 adsorption, 8 coagulation, 9 electrolysis, 10 and ion-exchange, 11 although these processes require complicated devices, and the carriers cannot be recycled for further applications.…”
Section: Introductionmentioning
confidence: 99%